Tourist Preferences for Hotels and Accommodation in Samosir Regency Based on Online Review - Siregar, Roswani; Subagiharti, Heni; Syafitri Handayani, Diah; Sofyan, Ahmad (International Journal of Travel, Hospitality and Events, 2024)
Purpose: This study aims to uncover tourist preferences for various accommodation types, including hotels in Samosir Regency. These preferences include attractiveness, facilities, and hospitality. Research methods: This study uses a qualitative approach through secondary research with data collection from online reviews. The sample consists of 50 accommodations in Samosir Regency based on Google Reviews with ratings > 3.0 and more than 30 reviewers. Data was collected by searching on google.com/travel with a total search result or population of 118 items, and a sample of 50 was obtained using the purposive method with the provisions of the Google Review Summary where the Rating Review was > 3.0; and the Number of Reviews >30 reviewers. Data were analyzed based on the Component Review using a Likert scale for 3 elements of the tourism industry, namely (1) Attraction that consists of atmosphere, location, and property; (2) Facilities consisting of Amenities, Bathrooms, and Bedroom; and (3) Hospitality which consists of Service, Cleanliness, and Food. Result and discussion: The analysis result revealed that the element of attraction shows a very satisfying preference from tourists. In second place is a satisfying preference for hospitality elements. Meanwhile, the facilities element shows the lowest preference or is unsatisfactory. This description of preferences shows that among the elements of tourism, improving the quality of hotel/accommodation facilities can be the biggest priority in efforts to develop tourism in Samosir Regency in providing high satisfaction and return visits. Implication: As a tourist destination, Samosir Regency, which relies on the Lake Toba area, has experienced an increase in tourist visits from year to year, both foreign and local tourists. This is facilitated by the general public's access to information and locations using information technology and the Internet.